The Effectiveness of Employing AI Public Relations Practitioners in Government Institutions: A Survey Study (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify how public relations practitioners employ artificial intelligence in government institutions, uncover the reasons for their use of AI technologies and tools in government institutions, and examine their attitudes toward the use of AI technologies in government institutions.The study is a descriptive study and utilizes a survey approach. The study sample consisted of (78) male and female public relations practitioners working in government institutions in the Kingdom of Saudi Arabia. A questionnaire was used as a data collection tool.The study reached a set of results, the most notable of which were: The motive "to save time and effort" topped the list of reasons why public relations practitioners used AI technologies and tools in Saudi government institutions, with an arithmetic mean of 2.70. Second was "to facilitate the process of extracting valuable information from big data," with an average of 2.68. Automated responses topped the preferences of the study sample's public relations practitioners for AI technologies and tools used in institutions, with an arithmetic mean of 1.72. Data analysis technology came in second place, followed by administrative process automation in third place.
Keywords: Public Relations; Artificial Intelligence; Saudi Government Institutions; Public Relations Practitioners